Barriers to Accessing Addiction Treatment for Women at Risk of Homelessness - Rizzo, Davinia; Mu, Temika; Cotroneo, Sophia; Arunogiri, Shalini (Frontiers in Global Women's Health, 2022)
Women remain under-represented in addiction treatment, comprising less than a third of clients in treatment services. Shame, stigma, and fear of legal and social repercussions, for example, child protection involvement, are major barriers impacting on treatment-seeking for women. This is compounded for women at risk of homelessness, with practical and logistical reasons for not engaging in treatment. We conducted a qualitative study with both clinicians and service-providers, and women with lived experience of addiction and at risk of homelessness, to identify barriers to access and help-seeking within this vulnerable population. Adult women with lived experience of homelessness and addiction were invited to participate in an online focus group. Interviews were transcribed and analysed using framework analysis. Analysis resulted in the identification of barriers to access in three areas. These were system-related, socio-cultural, and emotional barriers. We also present findings from the focus group recorded in real-time, by the novel method of digital illustration. This study highlights key factors impacting on help-seeking and access to treatment for addiction faced by women at risk of homelessness. Findings are discussed in the context of exigent literature. The findings of this study highlight important areas of consideration for clinicians and service-providers working with women who experience addiction, as well as informing future research directions for this priority population.